Alternative Public Spaces in Hybrid Media Environments: Dissent in High Uncertainty. (September 2021) - Issawi, Fatima el
Independent news websites and press played a vital role in creating spaces of contention in the context of the Moroccan pro-democracy movement of 2011. This article looks at the role of this press in disseminating alternative narratives in the hybrid media and political environment that followed the pro-democracy movement. Based on extensive interviews with journalists, this article examines journalists' practices in countering hegemonic media and political discourse, to understand how they contribute to—or hinder—the formation of counter publics under tough repression. The article uses the critical frameworks of dominant and counter-publics and Judith Butler's concept of silencing.